Studi Faktor-Faktor Keterlambatan Proyek Pada Kontraktor di Daerah Istimewa Yogyakarta - Farlianto, Farlianto Farlianto (JURNAL ILMU MANAJEMEN, 2015)
This study is aimed to investigate the antecedent of the project deleyed of contractors work. Various antecedent are explored both partially and simultanously. Sample are gathered from the site managers of Dinas Pengairan dan Dinas Bina Marga for DIY project. The result shows that a lot of antecedent such as work document aspect, inspection system, job control and evaluation, organizational system, Coordination and communication, other uncontrolable aspect, the readiness of resourches, and the work planning and schedulling aspect are related to the deleyed of project. The implication of the results are discussed.